Urinary peritonitis secondary to suprapubic bladder puncture: some details regarding the micro-size technique - di Leoni, Francisco; Cazabán, Luis A; García Guido, Luis (Cirugía del Uruguay, 1976)
The case of a urinary peritonitis following a suprapubic trocar cistostomy is described. It was due to a defective technique in the performance of the procedure. Att.ntion is called to the technical details of it, in order to avoid this complication.